COMPARATIVE RESEARCH: IMPLEMENTATION ANALYSIS OF AUDIOVISUAL MEDIA IMPLEMENTATION IN SOCIAL STUDY SUBJECT IN UNITED STATES OF AMERICA AND TURKISH - Wirawan, Gandung; Hurri, Ibnu; Pandikar, Ernandia (Universitas Pendidikan Indonesia, 2018)
This study presents the results of literature analysis on the application of audiovisual media in IPS learning in the United States and Turkey. The analysis is done so that the differences and advantages of audiovisual media used by each country can be known. This research uses literature method by tracing the sources of journals, scientific magazines, books, and internet sources. The results show that the United States and Turkey are concentrated in the development of Social Study learning media-based audiovisual. In addition, the use of audiovisual media in Social Study in the United States and Turkey can create a more active, innovative, creative, and fun learning atmosphere for learners.